Consequences Of Early Extraction of Deciduous Teeth in Children - Kamalova Feruza Rahmatillaevna; Safarov Sherzod Umarovich (Genius Journals, 2021)
Temporary teeth play a very important role in the bite formation process. They are considered to be conductors for the growth of permanent teeth. It is the temporary teeth that pierce the strong bone tissue and form the bed for the eruption of molars, which exactly follow the growth of their predecessors. That is why it is important that the temporary teeth are not only healthy, but also grow in the right direction, so that later the child would not have problems with bite
Keywords: Teeth; bite; children; dental arch